Priložnosti za uspeh: priročnik za vzgojitelje in učitelje pri delu z otroki in mladostniki, ki prihajajo iz drugih kulturnih okolij - Licardo, Marta; Golob, Nikolaja (2017)
Opportunities for success: the guide for preschool teachers and teachers in elementary and upper secondary education, who work with children and adolescents coming from other cultural backgrounds. The guide is for preschool teachers and teachers in elementary and upper secondary education, who work with children and adolescents coming from other cultural backgrounds. In the introduction part are presented most common problems and issues, together with protective factors, which support successful work with immigrant children and form base for inclusive intercultural learning environment. The middle part of the guide is overview of the guidelines for professionals who work with immigrant children in preschool, elementary and upper secondary education. Legislation guidelines, actual issues and solutions are presented for each education level, together with various methods and recommendations, hot to successfully include immigrant children and parents to Slovenian education system. Special chapter is ICT didactical material for professionals who work with immigrant children and students, which is the result of project work and testing of the iTMS system. The guide also includes chapters with useful links to various didactical tools and materials and basic specifics of countries from where immigrant children in Slovenia most often come from.
Keywords: immigrants; education; didactics; preschool; school; teachers